SARON DEMUNGÃ¢â¬â¢S TIMBRE AND SONOGRAM OF GAMELANS GUNTURMADU FROM KERATON NGAYOGYAKARTA - Kuswanto, H. (Jurnal Pendidikan Fisika Indonesia, 2012)
Penelitian ini bertujuan untuk mempelajari spectrum warna bunyi (timbre) dan sonogram dari Saron Demung Gamelan Gunturmadu dari Keraton Ngayogyakarta. Suara setiap wilahan direkam dengan bantuan pengolah suara yang ada pada komputer. ÃÂ Akurasi frekuensi yang dapat diperoleh dengan pengolah ini adalah 1 Hz. Frekuensi dasar dari saron demung gamelan Gunturmadu untuk setiap wilahan #1 sampai dengan #7 masing-masing adalah 197, 207, 221, 261, 285, 304, 326 Hz. Lokasi frekuensi harmonik ÃÂ tidak berturutan akan tetapi disisipi dengan frekuensi tak harmonis. Jumlah frekuensi harmonis dan tak harmonis yang membentuk warna bunyi untuk setiap wilahan berbeda. Ketebalan garis frekuensi dasar pada sonogram bertahan lebih lama dibandingkan dengan frekuensi lain pada suatu wilahan.The aim of this research is to study the timbre spectrums of Saron Demung instruments of gamelans Gunturmadu of Keraton Ngayogyakarta. This gamelan, as a set of traditional Javanese ensemble, are a pelog scale, seven scale in one octave. Sound of Saron Demung instruments are recorded by sound software. This software can display waveform in time domain and spectrum in frequency domain. The fundamental frequency is shown directly by software. ÃÂ Other peak frequencies can be traced by shifting the cursor on top of it. The accuracy of frequency that can be produced is 1 Hz. Fundamentals frequencies of ÃÂ Saron Demung ÃÂ keys ÃÂ #1 to #7 of gamelan Gunturmadu are 197, 207, 221, 261, 285, 304, 326 Hz respectively. The location of the harmonic frequencies are not always consecutive, but sometimes punctuated by another frequency. The numbers of harmonics and inharmonic frequencies of each keys are different. The thick lines of the fundamental frequency in sonogram exist in longer time than the other.